Mapping the ascendance of the 'living wage' standard in non-state global labour codes. (3rd April 2015) - Doorey, David J.
Abstract : The living wage standard has emerged as a norm in global initiatives targeting supply chain labor practices. This is unexpected, because the living wage, if actually paid, could impose substantial new supply chain costs. There is also considerable disagreement on how to calculate a living wage in practice. Therefore, the story of how the living wage ascended to become a standard term found in global labor supply chain initiatives provides an interesting case study on how norms and standards emerge through the complex interplay of transnational business governance (TBG) interactions. The subject of TBG interactions is an emerging field of study. These interactions are complex, involving multiple public and private actors crossing vast geopolitical spaces, with sometimes shared, but often conflicting interests. This complexity makes TBG interactions both an exciting new field of inquiry for scholars, but also an extremely challenging one. In these early days of theory development, it is useful to engage in a mapping exercise that will help scholars identify and test the relationships between the many inputs and outputs of TBG interactions. This paper contributes to this exercise by proposing and developing a basic open systems framework for analyzing TBG interactions. This new systems framework is demonstrated by reference to the complex story of the 'living wage' standard in private governance schemes targeting labour practices in global supply chains.